Physical Humanlikeness as A Moderator of The Relationship Between AI Influencer Marketing and Purchase Intention - Rahyono Rahyono; Ayu Nursari; Lestari Wuryanti; Reza Hardian Pratama (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The purpose of this study is to examine the role of AI influencers in enhancing social media user experience, strengthened by physical human likeness as a moderating variable to reinforce the purchasing experience. This study employs a quantitative method with a sample of 250 respondents who have experience in purchasing through artificial intelligence. The data analysis technique used is SEM-PLS, conducted using SmartPLS 4.0. Artificial intelligence improves customer interaction and engagement, which in turn increases purchase intention. Additionally, Companies should integrate human-like elements into AI services, such as more empathetic communication styles, personalized responses, and the ability to capture customers’ emotional context. This approach enhances customer engagement and experience, ultimately increasing purchase intention. This study extends the literature in AI marketing by demonstrating that the success of AI is not solely dependent on technological advancement, but also on its ability to create interaction experiences that resemble human interactions.